Inovasi Layanan Kependudukan Melalui Program Jemput Bola di Dinas Kependudukan dan Catatan Sipil Kabupaten Tangerang - Anggita May Putri Kiswanto; Marissa Krianayanti Bunga Putri; Vivi Charunia Wati; Regi Rizki Fauzi; Irvan Arif Kurniawan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Public administration focuses on the implementation of government through effective management, including in public services. The Population and Civil Registration Office of Tangerang Regency launched the Jemput Bola Program as an innovation in population administration. This program aims to overcome obstacles to access to services for the community, especially those who live in remote areas or have physical limitations. Through a proactive approach, Disdukcapil officers visit the community to provide services, such as making Identity Cards (KTP), Family Cards (KK), and birth certificates. This study uses a qualitative approach to analyze the implementation of the Jemput Bola Program and its impact on the quality of population administration services. The theory of diffusion of innovation by Everett M. Rogers is used as an analytical framework, focusing on five characteristics of innovation: relative advantage, appropriateness, complexity, trialability, and ease of observation. The results of the study indicate that the Jemput Bola Program provides significant benefits in terms of accessibility and speed of service. The community feels real benefits from this program, which also contributes to more accurate population data updates.